Black and white complainants and the police: A comparison of individual and contextual characteristics - Decker, Scott H. (American journal of criminal justice, 1985)
Citizens have always had an important role in the crime control process; they are most often responsible for the detection of crime. It is imperative, therefore, that citizens perceive police officers to be competent and just in the execution of their duties; in the absence of such confidence, the process suffers. Ironically, the groups which are most often the victims of crime hold the most negative attitudes toward the police. Minorities in urban communities, particularly blacks, fit this pattern. These attitudes appear to be linked to the perception of negative, differential experiences with the police, experiences which often lead to the filing of a formal complaint. Using a data set from the complaint files of a large American city, this article explores the relationship between the attitudes of blacks toward the police, experiences with the police, and complaints lodged against the police.